Is the oral labor process a discussion of case theory from which the judge resolves? - Calonge Rojas, Roque David (2021)
On January 15, 2010, Law No. 29497, New Labor Procedure Law, was published in the Official Gazette El Peruano, thus implementing a new form of litigation in Peru, and introducing two tools or groups of tools that allow the application of the new procedural instrument: information technology and oral litigation techniques. Indeed, the use of information technology, placed at the service of the administration of justice, and the use of oral litigation techniques, as a new litigation tool, constitute the new rules of the game, which allow lawyers, on the one hand, to formulate their case theories, from which they support their claims; and the court, on the other hand, to resolve the conflict, in the face of the case theories, exposed by the parties.